Broadband generation of accelerating polygon beams with large curvature ratio and small focused spot using all-dielectric metasurfaces - Chen, Lei; Kanwal, Saima; Lu, Yongzheng; Zhang, Dawei; Chen, Xu; Chen, Jian; Wen, Jing (Nanophotonics (Berlin, Germany), 2022)
Self-accelerating polygon beams have drawn growing emphasis in optics owing to their exceptional characteristics of multiple self-accelerating channels and needle-like field distributions. Various approaches have been proposed to generate polygon beams, such as using spatial light modulators (SLMs) or plasmonic metasurfaces. However, SLMs impede the miniaturization of the optical system and both approaches are subject to low efficiencies and demand an extra physical lens with a long focal length for Fourier transform, which limits the quality and the diverse variability of polygon beams. In this article, we demonstrate the generation of high-quality accelerating polygon beams in broadband spectra of 500–850 nm by utilizing dielectric metasurfaces. These metasurfaces integrate the functionality of the Fourier transform lens to enable the resulting beams with a large curvature ratio for the self-accelerating channels and a relatively small size for the autofocus region. The curvature ratio of the beam at = 633 nm is 31 times higher than the previously reported plasmonic-based method. While the size of the focused spot is 2.35 µm, which is reduced by nearly 15 times. The proposed beam generator provides ample opportunities for applications such as particle micromanipulation, beam shaping, laser fabrication, and biomedical imaging.